2006
DOI: 10.1080/00437956.2006.11432563
|View full text |Cite
|
Sign up to set email alerts
|

The role of mood marking in complex sentences A case study of Australian languages

Abstract: Abstract. This study investigates the role of mood markers in the semantic composition of complex sentence constructions, on the basis of a sample of Australian languages. The question of mood marking in complex sentences is theoretically significant because it involves a clause-internal category that plays a crucial role in the semantics of a construction above the level of the individual clause. Previous work on mood in complex sentences has shown that presence of mood marking in one of the component clauses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Ngalakan (Merlan 1983 From a cross-linguistic perspective, it has been shown that Mesoamerican languages tend to have avertive markers which are relational (Olguín Martínez 2022b). On the other hand, languages spoken in Australia and Papunesia tend to have avertive markers which are intraclausal (Verstraete 2014;Angelo and Schultze-Berndt 2016;Lichtenberk 1995). Amazonian languages show an interesting typological picture in that they tend to have avertive markers which may be intraclausal or relational.…”
Section: Avertive Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Ngalakan (Merlan 1983 From a cross-linguistic perspective, it has been shown that Mesoamerican languages tend to have avertive markers which are relational (Olguín Martínez 2022b). On the other hand, languages spoken in Australia and Papunesia tend to have avertive markers which are intraclausal (Verstraete 2014;Angelo and Schultze-Berndt 2016;Lichtenberk 1995). Amazonian languages show an interesting typological picture in that they tend to have avertive markers which may be intraclausal or relational.…”
Section: Avertive Markersmentioning
confidence: 99%
“…Avertive markers may be 'relational' or 'intraclausal' (Verstraete 2014). By 'relational' is meant conjunctions that only appear in biclausal constructions, and by 'intraclausal' is meant markers which occur in monoclausal constructions and have also the potential to contribute to the semantics of complex sentence relations (Verstraete 2014: 195).…”
Section: Avertive Markersmentioning
confidence: 99%
“…Alongside these investigations of complex predicates and verbal classification stand a significant number of studies of gender and nominal classification (Harvey and Reid 1997; Nicholls 2007). Other topics recently attracting attention to the semantics–morphology interface include epistemology (Mushin 1995), volitionality (and the rarity of its explicit encoding –Dixon 2002: 57) and mood (Verstraete 2005, 2006, forthcoming a).…”
Section: Morphology and Word Classesmentioning
confidence: 99%